The Effect of Memory Games Therapy on the Cognitive Function of Older Adults - Basuki, Hyan Oktodia; Oktafia, Siti Herlinda; Suhartono; Pitaloka, Dyah; Widyawati, Mei; Hakim, Lukman; Faizah, Hanim Nur; Nurhadi, Mokhamad; Fauziansyah, Ahmad (Babali Publisher, 2025)
Introduction: Cognitive function in older adults often declines, particularly affecting short-term memory. Older adults may also experience difficulties in learning new information, adapting to changes, and recognizing people, places, and objects. One approach to improving cognitive function is memory games therapy. This study aims to examine the effect of memory game therapy on the cognitive function of older people. Methods: This research employed a quasi-experimental design using a one-group pre-test and post-test approach. The study was conducted in September 2024 in Tuban Regency. The population consisted of 36 older adults experiencing cognitive decline, and a sample of 33 participants was selected using a purposive sampling technique. The research instrument was the